A General Synthesis of Crumpled Metal Oxide Nanosheets as Superior Chemiresistive Sensing Layers. (6th June 2019) - Kim, Rheehyun; Jang, Ji‐Soo; Kim, Dong‐Ha; Kang, Joon‐Young; Cho, Hee‐Jin; Jeong, Yong Jin; Kim, Il‐Doo
Abstract: Metal oxide nanosheets having high mesoporosity, grain size distribution of 5–10 nm, and ultrathin thickness have attracted much attention due to their intriguing properties such as high surface‐to‐volume ratio and superior chemical activities. However, 2D nanostructures tend to restack, inducing a decrease in accessible surface area and a number of pores. To solve this problem, herein, a unique synthetic method of crumpled metal oxide nanosheets using spray pyrolysis of metal ion–coated graphene oxide, followed by heat treatment, is reported. This method is applicable not only to single‐component metal oxides but also to heterogeneous multicomponent metal oxides in which composition can be controlled. Crumpled SnO2, ZnO, and Co3 O4 as well as SnO2 /ZnO and SnO2 /Co3 O4 nanosheets with heterogeneous interfaces are successfully synthesized and used as superior gas sensing layers. Because of the abundant reaction sites, well‐developed porosity for high gas accessibility, the formation of heterojunctions, the crumpled SnO2 /ZnO and SnO2 /Co3 O4 nanosheets exhibit outstanding sensing performance ( R air / R gas = 20.25 toward 5 ppm formaldehyde, and R air / R gas = 14.13 toward 5 ppm acetone, respectively). This study can contribute to the realization of a family of heterogeneous crumpled metal oxide nanosheets that can be applied to various research fields. Abstract : A general synthetic platform of hierarchically structured holey metal oxide nanosheets is achieved via a graphene oxide templating route and spray pyrolysis technique. The crumpled heterogeneous 2D metal oxide (crumpled H_2D MO) as a sensing layer exhibits improved sensing performance of formaldehyde (crumpled 2D SnO2 /ZnO) and acetone (crumpled 2D SnO2 /Co3 O4 ) molecules due to the high porosity, surface area, and heterojunction effect.